Right to Social Security of the Older People in Bangladesh: A Focus on Human Rights Violation - Hossain, Md. Zahid; Haque, A. K. M. Mahmudul; Ullah, S. M. Akram (Social Inquiry: Journal of Social Science Research, 2021)
As the part of vulnerable groups, older people hold the rights to social security according to the Constitution of the People’s Republic of Bangladesh and the Universal Declaration of Human Rights (UDHR). This study is launched for the purpose of revealing the picture of the facts and figures of the deprivation of social security as a human rights violation of the older people in Bangladesh. The study is based on both primary and secondary sources of data. It reviews the social security programs regarding older people such as, old age allowance, widow allowance and disability allowance. The study finds that the government has taken several programs, but these programs have not been successful in achieving targets due to corruption, nepotism and inadequate national economy. Most of the older people of Bangladesh cannot properly enjoy the right to social security. For raising awareness about rights and responsibilities, enhancing proper ethical education can be helpful to remove the obstacles. Raising a massive social movement against corruption and nepotism can also be helpful as the beacon of hope in the way of ensuring social security of the older people in Bangladesh.